ROLE OF THE MEANS IN DANCE IN THE EDUCATION OF PSYCHOMOTILE SKILLS FOR PRETEENAGERS - Buftea Victor; Salup Mărioara; Iacob Anca (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Musical accompaniment is a part of the concept of music education, and any move away from compliance music performance efficiency entails minimizing the proposed motile content. The selection of the operational models and their application under the musical accompaniment for the purposes of rhythm education and motyle musicality contributes to efficient education and in the same time for the optimization of the dance lesson in the specialized clubs.